A comparative study of anti-slavery in 19th century Middle East and North Africa: the cases of the Egyptian Khedivate and the Husaynid Beylik of Tunis - Kim, Seong Hyun (AUC Knowledge Fountain, 2020)
In the nineteenth century, the polities in the Middle East and North Africa encountered the British pressure to abolish the slave trade and slavery. While the Khedivate of Egypt and the Husaynid Beylik of Tunis faced the same pressure, the internal causes of them such as a diplomatic motive also led them to adopt anti-slavery policies. However, despite the similar motivations and conditions, their practical measures against the slave trade and slavery showed apparent differences. Saʿid (r. 1854-1863) and Ismaʿil (1863-1879) of the Egyptian Khedivate took many measures against slavery and the slave trade, but their orders or decrees lacked detailed plans before the ultimate termination of the slave trade was announced in 1877, as a result of the Anglo-Egyptian convention. That convention was arranged only two years before the abdication of Ismaʿil and the convention did not specify the full abolition of slavery itself. As for the anti-slavery process of the Tunisian Beylik, Ahmad Bey (r. 1837-1855) took measures against slavery at a rapid pace. He prohibited the slave trade in 1841 and abolished slavery itself in 1846. The immediate and complete liberation of all slaves in 1846 was not attempted in the Khedivate of Egypt before it became a protectorate of the British Empire. This thesis attempts to find the major factors which influenced their different measures. For this purpose, three major differences between two polities in the scale of the slave trade, the presence of organized slave traders, and the government’s demand for slaves are compared. A comparison of the anti-slavery policies in two states that otherwise have multiple similar conditions will suggest the reasons for different paces and procedures of state-led anti-slavery efforts that can be applied to other polities. This comparison also may reveal to some extent how a state project during this period could be influenced by other state projects, their specific characteristics, and the interest groups related to those projects.